Angelman Syndrome without Chromosome Anomaly - J Gordon Millichap (Pediatric Neurology Briefs)
The clinical manifestations of Angelman syndrome (AS) in 12 patients without a cytogenetic or molecular defect and 28 with a deletion were compared at the Department of Neurology, Leiden University Medical Center, and other hospitals in the Netherlands.